Novel active food packaging films based on whey protein incorporated with seaweed extract - Andrade, Mariana A. (2021)
no 17921 Call no. 33/SI/2015 Centro-01-0145-FEDER-000018 SFRH/BD/138730/2018 2016/iFILM/BM UIDB/04077/2020 UIDB/00211/2020 UIDB/50006/2020 UIDP/50006/2020